Study of the Effect of Drying on the Pore Structure and Rate of Oxygen Consumption and Heat Release of Immersed Lignite - Wei Guo; Chunhua Zhang; Ziwen Dong; Yongliang Han (Geofluids)
To reveal the influence mechanism of the drying process of immersed coal on the spontaneous combustion characteristics, we measured the pore structure of coal with low-field nuclear magnetic resonance and conducted the temperature-programmed spontaneous combustion experiment. The results showed that the pore volume content of the pores with pore sizes of less than 100 nm was significantly reduced. The diameter range of 100–1000 nm was gradually generated after 8 h of coal drying, and the proportion of large pores and cracks larger than 1000 nm increased significantly during the drying process of the immersed coal. The oxygen consumption rate and the heat release rate were significantly affected by the degree of dryness and the temperature of coal samples in the temperature-programmed process. The turning point temperature was 140°C; below the turning point temperature, the raw coal had the fastest oxygen consumption and maximum heat release. When the coal temperature was higher than 140°C, the oxygen consumption rate and the heat release rate of the coal sample that was dried for 24 h were higher than those for the raw coal, followed by the samples that were dried for 8 h and dried for 48 h. The main reason is that the water content of the coal sample decreases to 11.4% and the porosity increases to 16.5% after drying for 24 h, while the proportion of pores or cracks larger than 1000 nm increases significantly to 87.17%, the largest increase range and the pore connectivity will reach the maximum.